Olfactory and Taste Disorders in Patients Suffering from Covid-19, a Review of Literature - Kimia Ghods; Arezoo Alaee (Shiraz University of Medical Sciences, 2022)
Corona virus epidemic has caused a widespread disaster around the world. In studies, there are pieces of evidence of olfactory and taste dysfunction in patients with Covid-19. These symptoms occur independently or can be associated with other symptoms such as dry cough. The mechanism of the above-mentioned disorders and their clinical features in patients are not yet known. The rate of incidence of olfactory dysfunction in patients has been varied from 29.64% to 75.23% and the rate of incidence of taste dysfunction among the people can be different from 20.46% to 68.95%. Therefore, clinicians including ENT specialists and dentists should pay attention to the symptoms of anosmia and ageusia in these patients to prevent delayed diagnosis and inappropriate treatments. In this review article, data have been collected by searching the available articles in the domestic and foreign journals using databases such as PubMed, PubMed Central, Medline, EBSCO, Google Scholar, and Embase with key words of Anosmia, Ageusia, Dysgeusia, Covid-19, and Coronavirus from 2019 to 2020. Among the relevant references, 38 authoritative articles were chosen. The data showed that it seems olfactory and taste function disorders are the obvious symptoms of Covid-19, which can occur independently or with other symptoms, but the pathogenesis is not well specified yet. Therefore, further studies are required to achieve a reliable result in this area.